Characterization of persistent headache attributed to past stroke - Rêgo, André; Pinheiro, Rita; Delgado, Sofia; Bernardo, Francisco; Parreira, Elsa (Arquivos de Neuro-Psiquiatria, 2022)
Background Persistent headache attributed to past stroke (PHAPS) is a controversial entity, recently included in the third edition of the International Classification of Headache Disorders (ICHD-3) despite being described only in retrospective studies.Objective To determine the frequency and characteristics of PHAPS in patients admitted with acute stroke.Methods We selected all patients with headache associated with acute stroke (HAAS) from a prospective, single-center registry of patients with acute stroke admitted to a Neurology ward between November 2018 and December 2019. We analyzed demographic, clinical, and neuroimaging data. We assessed the follow-up with a phone call questionnaire at 6 to 12 months.Results Among 121 patients with acute stroke, only 29 (24.0%) had HAAS. From these, 6 (5.0%) were lost to follow-up. In total, 23 (20.0%) patients answered the 6- to 12-month follow-up questionnaire and were included in this study. The median age of the sample was 53 years (interquartile range [IQR]: 38–78 years), and there was no sex predominance. Of the 10 patients (8,3%) that had persistent headache, 8 (6.6%) suffered from previous chronic headaches; however, they all mentioned a different kind of headache, and 1 (0,8%) probably had headache secondary to medication.Conclusions In the present study, only 10 out of 121 stroke patients (8.3%) referred persistent headache at the 6- to 12-month follow-up, but the majority already suffered from previous chronic headache, which raises the question that the actual prevalence of PHAPS may be lower than previously reported.
Keywords: Vascular Headaches; Headache Disorders, Secondary